2010
DOI: 10.1007/s00595-009-4005-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cancer with situs inversus totalis associated with KIF3 complex deficiency: Report of two cases

Abstract: Situs inversus totalis (SIT) is a relatively rare congenital anomaly, occurring at an incidence of 1 in 10 000-50 000 live births. Although there are some case reports of SIT with the presence of cancer, there are few reports on the relationship between SIT and cancer. However, the recent phylogenetic investigations of this condition suggest that this may be linked to the development and progression of cancer on the molecular level. The key elements are one of the intracellular motor proteins, the KIF3 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…Although this may potentially explain the occurrence of cancer in the patient with SIT assessed in the present study, no genes have been conclusively identified as candidates for this dual role to the best of our knowledge (16). The pathogenetic mechanisms underlying SIT were elucidated by previous studies, and it was shown that kinesin (KIF)3, an intracellular motor protein, has an important role in establishing left-right asymmetry (17). Nodal flow is autonomously generated by the rotation of cilia tilted toward the posterior of the cells of the ventral node.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although this may potentially explain the occurrence of cancer in the patient with SIT assessed in the present study, no genes have been conclusively identified as candidates for this dual role to the best of our knowledge (16). The pathogenetic mechanisms underlying SIT were elucidated by previous studies, and it was shown that kinesin (KIF)3, an intracellular motor protein, has an important role in establishing left-right asymmetry (17). Nodal flow is autonomously generated by the rotation of cilia tilted toward the posterior of the cells of the ventral node.…”
Section: Discussionmentioning
confidence: 76%
“…Information on multiple primary malignancies in patients with situs inversus or situs ambiguous (Table II), and cases of lymphoma and chronic granulocytic leukemia with situs inversus or situs ambiguous was provided (Table III). Although the occurrence of malignancy in patients with SIT may be coincidental, certain studies have suggested a possible association between malignancy and SIT (16)(17)(18). Previous studies have proposed that unidentified genes affecting the left-right axis arrangement may be associated with cancer susceptibility (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIT is a relatively rare anomaly that occurs at an incidence of 1 in 10,000 to 50,000 of the population [1]. Recently, in patients with SIT, laparoscopic surgery has been performed, including a laparoscopic cholecystectomy, laparoscopic exploration of common bile duct, laparoscopic sigmoidectomy, laparoscopic sleeve gastrectomy [3] and LADG [2-4].…”
Section: Discussionmentioning
confidence: 99%
“…Situs inversus totalis (SIT) is a relatively rare condition found in 1 per 10,000 to 50,000 persons [1]. SIT is an autosomal recessive congenital defect in which the position of abdominal and/or thoracic organs is a "mirror image" of the normal one, in the sagittal plane.…”
Section: Introductionmentioning
confidence: 99%